Is There Any International Diversification Benefits in ASEAN Stock Markets? - Lim, Kian-Ping; Liew, Venus Khim-Sen (Orebro University School of Business, 2009)
This study finds that there is a common force which brings all the five ASEAN stock markets together in the long run by the nonparametric tests. This suggests that shocks from any of these five markets may spillover to the other markets in the same region. The recent Asian financial crisis bears a good testimony to this ‘contagion effect'. Subsequently, there would be no long run gain from international portfolio diversification. Specifically, investors with long run horizons may not benefit from an investment made across the countries in this ASEAN region. One possible explanation for this intra-ASEAN stock markets integration is their strong economic ties, especially intra-ASEAN trade and investment that has indirectly linked their stock indices.